Application Influence of The Competitive Advantage Strategy and Total Quality Management Towards Corporation Performances (Study in The Manufacturing Corporation Certificates of ISO 9000 in East Java) - Gunarianto - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is aimed at obtaining empirical evidence and perfect understanding about influence phenomenas of the competitive advantage strategy application and Total Quality Management towards manufacturing corporation performances obtaining certificates of ISO 9000 in East Java.Contribution of this research is expected to be able to provide ideas about the scientific development in the fields of Strategic Management, Cost Management and Operational Management. Especially for corporations and professionals, this research is expected to provide contribution to the setting of strategic plan, application of Total Quality Management and performance appreciation using Balanced Scorecard perspective.Census research method is applied in this research. While the research type is descriptive-verificative. To test the hypothesis used method of Structural Equation Modeling and Principle Component Analysis is applied. Results of the descriptive analysis show that application influence of the competitive advantage strategy and Total Quality Management, towards corporation performances is proved to be categorically high. Application on each perspective existing in the Balanced Scorecard is also proved to be categorically high.Results of the hypothesis test show that application influence of the competitive advantage strategy towards corporation performance is 34%, application influence of Total Quality Management towards corporation performance is 21%. Simultaneously application influence of the competitive advantage strategy and Total Quality Management towards corporation performance is 91 %.This research implies that application of competitive advantage strategy, and Total Quality Management are proved to provide positive and significant contribution towards manufacturing corporation performance.Keywords: Competitive Advantage Strategy, Total Quality Management, Balanced Scorecard, Certificate of ISO 9000, Stretegic Busines Unit